Soy protein meets bioactive glass: Electrospun composite fibers for tissue engineering applications - Tansaz, Samira; Liverani, Liliana; Vester, Lars; Boccaccini, Aldo R. (Materials Letters, 2017)
Soy protein isolate (SPI) was used to produce electrospun nanofibers, intended for tissue engineering (TE) applications. For the first time electrospun composite fibers have been successfully fabricated by the addition of nano and micron-sized 45S5 bioactive glass (BG) powders to SPI solution. The influence of BG particles on electrospun fiber morphology and mechanical properties was investigated. Optimization of electrospun parameters with focus on environmental factors indicated the need to control humidity for SPI fibers fabrication.
Keywords: Soy protein isolate Electrospinning Bioactive glass Nanofibers Tissue engineering